PCOS WITH INFERTILITY AND ITS AYURVEDA MANAGEMENT - A CASE STUDY - Karandikar, Ashwini Narayan (International Journal of Ayurveda and Pharma Research, 2018)
PCOS (polycystic ovarian syndrome) is a complex disorder comprising of anovulation, hyperandrogenism and polycystic ovaries. It is the primary cause of infertility nowadays. In Ayurveda all gynecological disorders are explained under Yonivyapadas. Based on the principles PCOS can be diagnosed and treated as well. Following is a case study of a female having infertility due to PCOS. Her reports showed PCOS, right tubal block and unovulatory cycles. She was treated with different Ayurveda treatment modalities like Yoni dhavan (vaginal douche), Anuvasana and Niruha basti (oil and decoction enema) and internal medicines like Rasapachaka, Aarogyavardhini and Dashamoolarishta.